An 11-bp Indel Polymorphism within the CSN1S1 Gene Is Associated with Milk Performance and Body Measurement Traits in Chinese Goats - Zhang, Yanghai (Animals (Basel), 2019)
SIMPLE SUMMARY: In the field of animal breeding, selection using molecular genetic markers, such as insertions/deletions (indels), is a novel method to reduce the generation interval and more accurately improve performance. The casein alpha s1 (CSN1S1) gene is one of the major genes regulating the milk performance of mammals, and it is also relevant to body development. Previous studies have shown that an 11-bp indel in this gene was strongly associated with goat litter size, however, its effects on milk performance and body measurement traits have not been studied. In this study, this indel was genotyped in three Chinese goat breeds, and further analysis results revealed that this indel polymorphism was significantly associated with milk performance in dairy goats, as well as affecting the body measurement traits in all three breeds. These findings hint that the 11-bp indel within CSN1S1 gene could be utilized for effectively selecting goats with excellent performances in terms of production and breeding. ABSTRACT: The casein alpha s1 (CSN1S1) gene encodes α-s1 casein, one of the proteins constituting milk, which affects milk performance, as well as improving the absorption of calcium and bone development in mammals. A previous study found that an 11-bp insertion/deletion (indel) of this gene strongly affected litter size in goats. However, to our knowledge, the relationships between this polymorphism and the milk performance and body measurement traits of goats have not been reported. In this paper, the previously identified indel has been recognized in three Chinese goat breeds, namely the Guanzhong dairy goat (GZDG; n = 235), Shaanbei white cashmere goat (SBWC; n = 1092), and Hainan black goat (HNBG; n = 278), and the following three genotypes have been studied for all of the breeds: insertion/insertion (II), deletion/deletion (DD), and insertion/deletion (ID). The allele frequencies analyzed signified that the frequencies of the “D” allele were higher (47.8%–65.5%), similar to the previous report, which indicates that this polymorphism is genetically stable in different goat breeds. Further analysis showed that this indel was markedly associated with milk fat content, total solids content, solids-not-fat content, freezing point depression, and acidity in GZDG (p < 0.05), and also affected different body measurement traits in all three breeds (p < 0.05). The goats with II genotypes had superior milk performance, compared with the others; however, goats with DD genotypes had better body measurement sizes. Hence, it may be necessary to select goats with an II or DD genotype, based on the desired traits, while breeding. Our study provides information on the potential impact of the 11-bp indel polymorphism of the CSN1S1 gene for improving the milk performance and body measurement traits in goats.